Sodium iron phosphate pyrophosphate positive electrode material and preparation method thereof and battery
Through segmented low-temperature presintering and carbon coating technology, the problem of difficult removal of crystallized water and decomposition products in the positive electrode material prepared by hydrothermal reaction is solved, and the compaction density and electrochemical properties of the material are improved.
Patent Information
- Application Number
- CN202510090078.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
In the prior art, when preparing the positive electrode material of sodium ferric pyrophosphate phosphate in hydrothermal reaction, it is difficult to completely remove crystal water or decomposition products, resulting in uneven distribution of crystal particles during sintering, affecting compaction density and electrochemical properties.
The staged low-temperature presintering step is adopted, and the crystallization water and decomposition products generated by the hydrothermal reaction are removed by performing two presinterings in the range of 60 to 300°C, and carbon coating is carried out before high-temperature sintering to ensure the uniformity of the carbon layer.
The uniformity of crystal particles is achieved, the compaction density and electrochemical properties of the positive electrode material are improved, and the rate performance and cycling properties of the material are improved.
Smart Images

Figure CN119528107B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and more specifically, relates to a sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof and a battery. Background Art
[0002] With the continuous consumption of fossil energy and the increasing importance of environmental protection, people's demand for green travel and low-carbon travel is gradually increasing. At present, in the field of electrochemical energy, the successful commercialization of lithium-ion batteries is more eye-catching. As a "rocking chair battery", sodium-ion batteries of the same family of elements are considered to be a supplement or even a substitute for lithium-ion battery technology with their similar working principles and similar battery structures. Especially with the rising trend of lithium prices in the past two years, unlike lithium, sodium is rich in resources and large in reserves, and its cost is significantly lower than that of lithium ore. At the same time, the industrial production line of sodium-ion batteries is compatible with existing lithium-ion production lines, which greatly accelerates its industrialization process.
[0003] Sodium-ion batteries are considered one of the most effective electrochemical energy storage systems due to their low cost, high safety and environmental friendliness. In sodium-ion batteries, the positive electrode material is the source of sodium ions for the entire battery to be inserted and removed. It is an important component of sodium-ion batteries and plays a decisive role in improving electrochemical performance, improving energy density and reducing the cost of the entire battery. As a positive electrode material for sodium-ion power batteries, sodium iron pyrophosphate Na4Fe3(PO4)2P2O7 (NFPP) material has the advantages of abundant raw material sources, low price, green environmental protection, long life, safety and good thermal stability, making it an ideal electrode material in the field of energy storage. However, the lower compaction density and theoretical specific capacity (about 129mAh / g) of NFPP affect its application range.
[0004] A Chinese patent with application number CN202311635063.X discloses a method for preparing a spherical sodium iron phosphate pyrophosphate positive electrode material, which comprises mixing a sodium source, an iron source, a phosphorus source and a solvent, performing a hydrothermal reaction to obtain a primary particle precursor, spray drying the precursor after mixing with a carbon source to obtain a spherical precursor, and finally sintering the precursor in an inert atmosphere. A spherical sodium iron phosphate pyrophosphate positive electrode material with good electrochemical properties is obtained by a simple hydrothermal reaction, spray drying and sintering. The application proposes to prepare a secondary spherical micron-sized sodium iron phosphate pyrophosphate positive electrode material after blending a primary particle precursor with a carbon source, which can provide more reactive sites while the spherical structure can also ensure the tap density of the positive electrode material, reduce internal resistance, and improve the rate performance and cycle performance of the positive electrode material. Usually, the traditional hydrothermal reaction intermediate needs to be sintered to remove the decomposition products after dehydration, and the decomposition products will be produced at different temperatures. One sintering often cannot remove various decomposition products well, resulting in uneven particle distribution of traditional NFPP positive electrode materials, affecting their compaction density, etc. Although the specification of the application mentions that the sintering process is to first heat up to 250-550℃ at a rate of 1-10℃ / min and keep it for 2-10h, and then heat up to 500-750℃ and keep it for 10-50h, that is, segmented sintering is adopted, but the purpose of doing so is not pointed out, and according to existing research, the sintering temperature of sodium iron pyrophosphate (NFPP) positive electrode material is usually 450-650℃ during the preparation process. Therefore, it can only be considered that the application is a conventional process adjustment based on actual working conditions, and the above sintering temperature still refers to the sintering process of NFPP in the prior art. However, during the sintering process at high temperature, decomposition products and crystallization water may not be removed well, resulting in uneven crystal growth. In addition, only one carbon source is added in the two-stage sintering. Although spray drying can make the carbon source and the primary particle precursor blend more evenly, this will still lead to uneven carbon coating, ultimately resulting in poor compaction density of the crystal particles and affected electrochemical performance.
[0005] The Chinese patent with application number CN202210847653.8 discloses a sodium ion battery positive electrode material sodium iron phosphate pyrophosphate / carbon and its synthesis method and sodium ion battery, the steps are: weighing sodium source, organic phosphonic acid, and iron source according to the sodium: iron: phosphonic acid molar ratio of 4:3:4 or 3:2:3, adding deionized water and stirring, continuing to add or not adding inorganic carbon source, heating and stirring to evaporate to dryness, drying the obtained solid, grinding, pre-sintering under nitrogen protection, naturally cooling, taking out and grinding again, and sintering under nitrogen protection, and naturally cooling to obtain the product sodium ion battery positive electrode material sodium iron phosphate pyrophosphate / carbon. The invention simplifies the synthesis process by using organic phosphonic acid as the phosphate, all or part of the carbon source required for the synthesis of sodium iron phosphate pyrophosphate / carbon, and makes the obtained electrode material have high specific capacity and long cycle life. It mentions the use of carbon coating to improve the electrochemical properties of the positive electrode material, and adds a carbon source before the reaction, and pre-sintering after the reaction. However, the specification states that the pre-sintering conditions are: pre-sintering for 5 to 10 hours at 300 to 400°C under nitrogen protection, and sintering conditions are: sintering for 8 to 12 hours at 550 to 650°C under nitrogen protection. In other words, although the application proposes a pre-sintering strategy, it also adds carbon and then sinters at a higher temperature, and does not specify what kind of intermediate is obtained after pre-sintering. It is still possible that the decomposition products cannot be completely removed, the grains grow unevenly, and the compaction density is poor.
[0006] In summary, in the process of preparing sodium iron phosphate pyrophosphate positive electrode materials by hydrothermal reaction in the prior art, the decomposition products of the preparation product of the hydrothermal reaction will adhere to the surface of the intermediate after drying, and cannot be removed well by one sintering, resulting in the traditional sintering process making the crystals of the NFPP positive electrode material uneven, affecting the compaction density of the positive electrode material. The prior art proposes that the strategy of carbon coating can be used to improve the electrochemical performance of the positive electrode material, but due to the influence of the particle size and size of the NFPP material itself, the uneven carbon coating will still cause the battery performance to decline. Therefore, how to overcome the poor morphology of the crystal particles and uneven carbon coating when preparing sodium iron phosphate pyrophosphate positive electrode materials by hydrothermal reaction, which in turn leads to poor performance such as material gram capacity and compaction density, has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0007] In view of the fact that when preparing sodium iron phosphate pyrophosphate positive electrode materials by hydrothermal reaction at present, it is inevitable that crystal water or other decomposition products cannot be completely removed at one time, resulting in uneven crystal particles in the sintering process, thereby affecting the compaction density, gram capacity and other properties of the positive electrode material. The purpose of the present invention is to provide a preparation method of sodium iron phosphate pyrophosphate positive electrode material, by setting up segmented low-temperature pre-sintering and other methods, so that the morphology of the crystal particles is better, the carbon coating is evenly distributed after sintering, and the sodium iron phosphate pyrophosphate positive electrode material with high compaction density and good capacitance is obtained.
[0008] In order to achieve these purposes and other advantages of the present invention, a method for preparing a sodium iron phosphate pyrophosphate positive electrode material is provided, comprising the following steps:
[0009] Step 1, hydrothermal reaction: adding the raw material into a Tris-HCl buffer solution, stirring evenly to obtain a mixed material, reacting, centrifuging, and obtaining a precursor; the raw material includes: a sodium source, an iron source, a phosphorus source, a first carbon source, and a first doping element;
[0010] Step 2, pre-sintering: pre-sintering the precursor under protective gas, first sintering at 60-150° C. for the first stage, and then heating to 150-300° C. for the second stage to obtain a pre-sintered intermediate;
[0011] Step 3, sand milling and spray drying: adding a second carbon source and a second doping element to the pre-sintered intermediate, sand milling and spray drying to obtain dry particles;
[0012] Step 4: high temperature sintering: sinter the dried particles at high temperature to obtain sodium iron pyrophosphate positive electrode material.
[0013] Preferably, in step 1, the pH value of the Tris-HCl buffer solution is 8-9; the stirring time is 5-30 min; the reaction temperature is 120-200° C., and the reaction time is 6-18 h.
[0014] Preferably, in step 1, the molar ratio of Na, Fe and P in the sodium source, iron source and phosphorus source is 1:0.75:1; the amount of raw material added is 30-50wt% of the mass of Tris-HCl buffer solution; and the molar ratio of the first doping element to Fe in the raw material is 0.001-0.002:1.
[0015] Preferably, in step 1, the sodium source is one or more of sodium carbonate, trisodium phosphate, sodium pyrophosphate, and sodium dihydrogen phosphate; the iron source is one or more of ferrous oxalate, ferrous phosphate, ferrous sulfate, and ferrous nitrate; and the phosphorus source is one or more of ammonium dihydrogen phosphate, phosphoric acid, and ammonium phosphate.
[0016] Preferably, in step 1, the first carbon source is one or more of glucose, sucrose, polyethylene glycol, and polyvinyl alcohol; and the first doping element is one or more of Mg, Ti, Cr, Zr, Al, V, Mn, Ni, and B.
[0017] Preferably, in the step 1, the mixed material is reacted in a polytetrafluoroethylene liner of a reaction kettle.
[0018] Preferably, in step 2, the protective gas is nitrogen, argon or an argon-hydrogen mixed gas; the first sintering time is 1 to 3 hours, during which the gas flow rate is 1 to 20 L / min; the second sintering time is 1 to 8 hours, during which the gas flow rate is 1 to 10 L / min.
[0019] Preferably, in the step 2, the carbon content of the pre-sintered intermediate obtained is 0.1-0.8 wt %.
[0020] Preferably, in step three, the second carbon source is one or more of β-cyclodextrin, chitosan, and sodium alginate; and the second doping element is one or more of Mg, Ti, Cr, Zr, Al, V, Mn, Ni, and B.
[0021] Preferably, in step three, the molar ratio of the second doping element to Fe in the pre-sintered intermediate is 0.0002-0.0006:1.
[0022] Preferably, in step three, the particle size D50 value is controlled by sand grinding to be 80 to 500 nm.
[0023] Preferably, in step three, spray drying is performed using a two-fluid spray gun or a centrifugal atomizer.
[0024] Preferably, when the two-fluid spray gun is used for spray drying, the specific process parameters are: inlet air temperature 200-260°C, outlet air temperature 80-120°C, and spray gun air source pressure 0.4-0.8 MPa.
[0025] Preferably, when the centrifugal atomizer is used for spray drying, the specific process parameters are: inlet air temperature 200-260°C, outlet air temperature 80-120°C, and atomizer frequency 360-400 Hz.
[0026] Preferably, in step 4, the high temperature sintering temperature is 450-600° C. and the time is 5-12 hours.
[0027] Preferably, in the step 4, the carbon content of the sodium iron pyrophosphate positive electrode material obtained is 1-2 wt %.
[0028] Preferably, the first doping element and the second doping element are selected from one or more of oxides, nitrates and acetates corresponding to the doping elements.
[0029] Preferably, the step three is replaced by: premixing β-cyclodextrin and B2O3 to obtain a β-cyclodextrin / B2O3 premix, adding the β-cyclodextrin / B2O3 premix to the pre-sintered intermediate, sand milling and spray drying to obtain dry particles; wherein the premixing method of β-cyclodextrin and B2O3 is:
[0030] S31, mixing a borate coupling agent, AEO-3 and anhydrous ethanol in a mass ratio of 1:0.3-0.8:40-80, stirring evenly, adding B2O3, ultrasonically treating at 40-70°C, 200-500W, 50-60kHz for 0.5-2h, standing at room temperature for 10-15h, and vacuum drying at 60-100°C to obtain modified B2O3; wherein the mass ratio of borate coupling agent, AEO-3 and B2O3 is 1:0.3-0.8:5-15;
[0031] S32. Mix the modified B2O3 and β-cyclodextrin, grind for 1 to 3 hours, heat treat at 150 to 300° C. for 0.5 to 2 hours under protective gas, and naturally cool to room temperature to obtain a β-cyclodextrin / B2O3 premix.
[0032] A sodium iron phosphate pyrophosphate positive electrode material is prepared by the above-mentioned method for preparing the sodium iron phosphate pyrophosphate positive electrode material.
[0033] A battery, wherein the positive electrode material of the battery is the sodium iron phosphate pyrophosphate positive electrode material as described above.
[0034] In the field of battery materials, the hydrothermal method is usually used to prepare crystals. In the process of preparing NFPP (Na4Fe3(PO4)2P2O7) by hydrothermal reaction, since it is usually carried out under high temperature and high pressure conditions, some reactants or intermediate products will decompose. For example, phosphates may decompose into orthophosphoric acid or other polyphosphoric acids, and some compounds may also generate corresponding hydrolysis products after hydrolysis reactions. Therefore, the prior art usually precisely controls the conditions of the hydrothermal reaction, and subsequently uses high-temperature sintering to remove or transform the decomposition products. However, after investigation, this application believes that the conventional high-temperature (>300°C) sintering cannot completely remove the crystal water or decomposition products produced during the reaction process, which ultimately leads to uneven distribution of crystal particles during the sintering process and poor compaction density of the positive electrode material. In this application, a low-temperature (60-300°C) pre-sintering step is designed after the hydrothermal reaction, and it is carried out twice. By limiting the process and temperature of the pre-sintering, the crystal water and other decomposition products produced by the reaction can be removed as much as possible, and crystal particles with uniform morphology can be obtained, so that the compaction density of the positive electrode material after sintering is better and the battery capacity is improved.
[0035] Further, in addition to limiting the temperature conditions of pre-sintering, the present application also makes the crystal particle morphology more uniform by controlling the carbon content of the intermediate obtained by pre-sintering. Since the carbon source has been added before the hydrothermal reaction, adding a low-temperature pre-sintering process can also remove the crystal water of the carbon source itself, so that the carbon source melts and decomposes, has good fluidity, and can be evenly blended with other raw materials, so that the carbon source can be pre-carbon coated on the intermediate for the first time during pre-sintering, and combined with doping to improve the electrical properties of the material, avoiding the situation where some areas are not coated during high-temperature sintering, further improving the electrical properties of the material, and using a small amount of carbon source for coating in advance can limit the excessive growth of grains in subsequent high-temperature sintering, further controlling the compaction density of the particles, and in this process, the carbon content of the obtained pre-sintered intermediate is 0.1-0.8wt% when the effect is best.
[0036] Furthermore, in the preparation method of the present application, in step 1, hydrothermal reaction, first, a Tris-HCl buffer solution is used as a solvent for the raw material, and the pH value of the hydrothermal reaction process is adjusted to be appropriate. Tris-HCl buffer solutions are commonly used in the fields of biochemistry and molecular biology, for example, as solvents for nucleic acids and proteins, to maintain the stability of the solution pH value without destroying the structure and function of these biological molecules. The present application chooses to use a Tris-HCl buffer solution in the hydrothermal reaction, which has relatively stable properties and has little interference with the hydrothermal reaction dominated by inorganic reactions, and will not generate side reaction products with the raw materials. It can stabilize the pH value and obtain a more uniformly crystallized precursor, which is beneficial to subsequent process operations.
[0037] Furthermore, the present application also controls the ratio between the Tris-HCl buffer solution and the raw materials, so that the addition amount of the above raw materials is 30-50wt% of the Tris-HCl buffer solution, which can maintain the pH value of the hydrothermal reaction process at about 8.5, keeping the reaction environment stable and not prone to failure. The precursor generated in this way has a high degree of crystallinity, which reduces the difficulty of subsequent sintering to remove other decomposition products, and is more conducive to improving the compaction density of the positive electrode material.
[0038] Secondly, in addition to adding a sodium source, an iron source, and a phosphorus source to the raw materials during feeding, the present application also adds a first carbon source and a first doping element, and stirs for 5 to 30 minutes to make the raw materials evenly mixed and fully contacted, so that the reaction can be complete, the appearance of by-products can be reduced, and the crystallinity of the precursor can be improved. The amount of sodium source, iron source, and phosphorus source added should at least meet the molar ratio of Na, Fe, and P in Na4Fe3(PO4)2P2O7 (NFPP) of 1:0.75:1. Since the carbon source does not participate in the hydrothermal reaction, after the hydrothermal reaction is completed, the first carbon source is blended with the crystal particles, which is convenient for the next pre-sintering process so that the first carbon source can be evenly coated on the surface of the crystal, realizing the pre-carbon coating of the pre-sintered intermediate and improving the electrochemical properties of the material. Generally speaking, the above raw materials are mixed and transferred to the polytetrafluoroethylene lining of the reactor to react at 120-200°C for 6-18h. Since the hydrothermal reaction needs to be carried out under high temperature conditions, the liquid in the reactor will vaporize and the pressure will gradually increase. The polytetrafluoroethylene lining is used, which can withstand high temperature (up to 230°C) and high pressure (up to 3MPa), ensuring that the reaction is safe and stable, and the generated crystal properties are more stable. In terms of raw material selection, the sodium source of this application is selected from one or more of sodium carbonate, trisodium phosphate, sodium pyrophosphate, and sodium dihydrogen phosphate, the iron source is selected from one or more of ferrous oxalate, ferrous phosphate, ferrous sulfate, and ferrous nitrate, and the phosphorus source is selected from one or more of ammonium dihydrogen phosphate, phosphoric acid, and ammonium phosphate. And the first carbon source is preferably one or more of glucose, sucrose, polyethylene glycol, and polyvinyl alcohol. The above carbon sources are selected as sintering materials in the pre-sintering stage, which can form a uniform and stable carbon layer under low temperature (60-300°C) sintering, improve the conductivity and ion diffusion rate of the material, and more preferably glucose. The first doping element is preferably one or more of Mg, Ti, Cr, Zr, Al, V, Mn, Ni, and B, and more preferably one or two of Mg and Ti. The conductivity of the electrode material can be improved by doping, and it is also added before the reaction. Doping before the hydrothermal reaction can make the crystallization more uniform, will not affect the uniformity of the particles during subsequent sintering, and has a better compaction density.
[0039] Then, in the second step of pre-sintering of the present application, the first stage of pre-sintering is carried out, maintained for 1 to 3 hours, during which the gas flow rate is 1 to 20 L / min, and then the second stage of pre-sintering is carried out, maintained for 1 to 8 hours, during which the gas flow rate is 1 to 10 L / min, to obtain a pre-sintered intermediate. The protective gas for pre-sintering is a single nitrogen or argon gas, or a mixture of argon and hydrogen. By controlling the gas flow rate and sintering time, the sintering process of the crystal particles is made more uniform. And after pre-carbon coating, a more uniform carbon layer can be formed during subsequent high-temperature sintering, avoiding the uneven carbon layer caused by one-step carbon coating, so as to improve the electrical properties of the material.
[0040] After sintering to obtain the intermediate, add the second carbon source and the second doping element thereto, sand grind and spray dry to obtain dry particles. The second carbon source is added, and the carbon coating modification is performed by adding the carbon source twice, so that the electrical properties of the positive electrode material are better, and the excessive growth of the grains in the subsequent sintering process is avoided, and the carbon coating is more uniform. In addition, after the secondary carbon supplementation and doping, the secondary doping elements can partially enter the material lattice to form bulk doping, and a small part of them can be combined with the secondary carbon source to form a carbon layer surface doping, thereby improving the capacity and other properties of the material. The preferred second carbon source is: one or more of β-cyclodextrin, chitosan, and sodium alginate, and β-cyclodextrin is more preferred; the preferred second doping element is: one or more of Mg, Ti, Cr, Zr, Al, V, Mn, Ni, and B, and B is more preferred; the above biomass carbon source and the second doping element are selected as the materials for the high-temperature sintering stage, so that the material can have more active sites after high-temperature sintering, and the performance is better.
[0041] Furthermore, the D50 value of the dry particles is controlled to be 80 to 500 nm, so that the pre-sintered intermediate can be uniformly mixed with the second carbon source and the second doping element in the form of fine particles, so as to achieve carbon coating and doping modification, improve the electrical properties such as the conductivity of the electrode material, and facilitate the subsequent sintering process. Generally speaking, the target product positive electrode material also needs to be crushed to obtain the required particles, and the present application controls the particle size and preferably uses a two-fluid spray gun or a centrifugal atomizer for spray drying to make the particle size of the dry particles uniform and appropriate, and the positive electrode material can be obtained without crushing after sintering, thereby reducing production costs and improving production efficiency.
[0042] Finally, the dried particles are sintered at 450-600°C for 5-12 hours, and the carbon content of the final target product, sodium iron phosphate pyrophosphate positive electrode material, is controlled to be 1-2wt%. Too high or too low a carbon content will affect its electrical properties. If the carbon content is too low, some particles will lack carbon coating on the surface, resulting in poor conductivity; if the carbon content is too high, the carbon coating will be too thick, affecting ion conduction. At the same time, the carbon content will also affect the compaction density. If the carbon content is too high or too low, the compaction density of the material will be reduced.
[0043] The present invention has at least the following beneficial effects:
[0044] 1. The present invention designs a low-temperature (60-300°C) pre-sintering step after the hydrothermal reaction in the preparation of the positive electrode material. The crystal particle morphology of the precursor is uniform through segmented pre-sintering, and the crystal water and decomposition products of the hydrothermal reaction are preferably removed, thereby controlling the compaction density of the material, and obtaining a high-density, high-capacity sodium iron phosphate pyrophosphate positive electrode material;
[0045] 2. The present invention uses Tris-HCl buffer solution to maintain the pH value of the hydrothermal reaction, which can make the reaction more thorough and form a more uniform precursor with higher crystallinity, thereby reducing the difficulty of subsequent sintering and impurity removal;
[0046] 3. In the preparation process of the present invention, the carbon source and the doping element are added twice, which improves the electrical properties of the positive electrode material, such as the conductivity, and makes the carbon coating more uniform during the sintering process, so that the morphology of the positive electrode material particles is better and the compaction density is improved;
[0047] 4. The present invention premixes the second carbon source and the second doping element so that they can be more evenly dispersed in the pre-sintered intermediate, making the crystal structure of the sodium iron pyrophosphate more stable, thereby further improving the electrochemical performance and compaction density of the sodium iron pyrophosphate positive electrode material.
[0048] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 The charge and discharge specific capacity diagram of the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 at 0.1C (1.7-4.3V);
[0050] Figure 2 This is the charge and discharge specific capacity diagram of the sodium iron pyrophosphate positive electrode material prepared in Example 1 at 1C (1.7~4.3V). DETAILED DESCRIPTION
[0051] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0052] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0053] Example 1
[0054] A method for preparing a sodium iron phosphate pyrophosphate positive electrode material comprises the following steps:
[0055] Step 1, hydrothermal reaction: prepare a Tris-HCl buffer solution with a pH value of 8.5, weigh 53g of sodium carbonate, 75.41g of ferrous phosphate, 37.98g of ferrous sulfate, and 115.29g of a 42.5wt% phosphoric acid aqueous solution according to a Na:Fe:P molar ratio of 1:0.75:1, mix with 3g of glucose (designed carbon content is 0.6wt%) and 0.0453g of MgO (Fe:Mg molar ratio is 1:0.0015), add to the prepared Tris-HCl buffer solution, the total mass of the above raw materials is 35wt% of the Tris-HCl buffer solution, stir for 10min to make it uniformly dispersed, obtain a mixed material, transfer the above mixed material to the polytetrafluoroethylene liner of the reactor, react at 150°C for 8h, centrifuge to remove the liquid, and obtain a precursor;
[0056] Step 2, pre-sintering: The above precursor is pre-sintered under nitrogen, first heated to 150°C and maintained for 2 hours, during which the gas flow rate is 15 L / min, and then heated to 280°C and sintered, maintained for 6 hours, during which the gas flow rate is 5 L / min, to obtain a pre-sintered intermediate with a carbon content of 0.6wt%;
[0057] Step 3, sand milling and spray drying: add 1.09 g of β-cyclodextrin and B2O3 (Fe:B molar ratio is 1:0.0004) to the above pre-sintered intermediate, perform sand milling, control the particle size D50 value to 400 nm, and then use a two-fluid spray gun for spray drying (inlet air temperature 240°C, outlet air temperature 100°C, spray gun air source pressure 0.6 MPa) to obtain dry particles;
[0058] Step 4: High temperature sintering: sinter the dried particles at 500°C for 8 hours to obtain a sodium iron phosphate pyrophosphate positive electrode material with a carbon content of 1 wt%.
[0059] Example 2
[0060] Step 1, hydrothermal reaction: prepare a Tris-HCl buffer solution with a pH value of 8.5, weigh 53g of sodium carbonate, 75.41g of ferrous phosphate, 37.98g of ferrous sulfate, and 115.29g of a 42.5wt% phosphoric acid aqueous solution according to a Na:Fe:P molar ratio of 1:0.75:1, mix with 4g of glucose (designed carbon content is 0.8wt%) and 0.0898g of TiO2 (Fe:Ti molar ratio is 1:0.0015), add to the prepared Tris-HCl buffer solution, the total mass of the above raw materials is 30wt% of the Tris-HCl buffer solution, stir for 10min to make it uniformly dispersed, obtain a mixed material, transfer the above mixed material to the polytetrafluoroethylene liner of the reactor, react at 180°C for 7h, centrifuge to remove the liquid, and obtain a precursor;
[0061] Step 2, pre-sintering: The above precursor is pre-sintered under nitrogen, first heated to 130°C and maintained for 1.5 hours, during which the gas flow rate is 15 L / min, and then heated to 300°C and sintered, maintained for 5 hours, during which the gas flow rate is 5 L / min, to obtain a pre-sintered intermediate with a carbon content of 0.8wt%;
[0062] Step 3, sand milling and spray drying: add 0.95 g of chitosan and B2O3 (Fe:B molar ratio is 1:0.0004) to the above pre-sintered intermediate, perform sand milling, control the particle size D50 value to 120 nm, and then use a centrifugal atomizer for spray drying (inlet air temperature 240°C, outlet air temperature 100°C, atomizer frequency 380 Hz) to obtain dry particles;
[0063] Step 4: High temperature sintering: Sinter the dried particles at 530°C for 7 hours to obtain a sodium iron phosphate pyrophosphate positive electrode material with a carbon content of 2 wt%.
[0064] Embodiment 3, 4
[0065] The implementation methods of Examples 3 and 4 are basically the same as those of Example 1, except that the material amounts and related process conditions are adjusted to a certain extent. The specific implementation conditions are shown in Table 1, and a sodium iron pyrophosphate positive electrode material with a carbon content of 1 wt% is obtained.
[0066] Table 1
[0067]
[0068] Example 5
[0069] The implementation method of Example 5 is basically the same as that of Example 1, except that in step 3, β-cyclodextrin and B2O3 are premixed to obtain a β-cyclodextrin / B2O3 premix, and then the pre-sintered intermediate is added; wherein the premixing method of β-cyclodextrin and B2O3 is:
[0070] S31, mixing borate coupling agent LD-100P, AEO-3 and anhydrous ethanol in a mass ratio of 1:0.5:50, stirring evenly, adding B2O3, ultrasonically treating at 50°C, 300W, 55kHz for 1h, standing at room temperature for 12h, and vacuum drying at 80°C to obtain modified B2O3; wherein the mass ratio of borate coupling agent LD-100P, AEO-3 and B2O3 is 1:0.5:10;
[0071] S32. Modified B2O3 (Fe:B molar ratio of 1:0.0004) and 1.09 g of β-cyclodextrin were mixed, ground in a grinder for 2 h, heat treated at 200°C for 1 h under nitrogen, and naturally cooled to room temperature to obtain a β-cyclodextrin / B2O3 premix.
[0072] Directly adding β-cyclodextrin and B2O3 to the pre-sintered intermediate affects the dispersibility, uniformity and stability of the doping due to its particle size, particle size distribution, viscosity and the like. In this embodiment, β-cyclodextrin and B2O3 are first premixed, and then mixed with the pre-sintered intermediate for sand milling and spray drying. Specifically, in the premixing process, B2O3 is first surface modified using a borate coupling agent (LD-100P) and a fatty alcohol polyoxyethylene ether (AEO-3) to effectively improve the dispersibility and surface activity of the material. Finally, β-cyclodextrin and modified B2O3 are ground and mixed, and a β-cyclodextrin / B2O3 premix with good dispersibility, uniformity and doping activity is obtained through heat treatment. The premix can be more evenly dispersed in the pre-sintered intermediate, inhibiting interface side reactions and making the crystal structure more stable, thereby further improving the electrochemical properties and compaction density of the sodium iron pyrophosphate positive electrode material.
[0073] Example 6
[0074] The implementation method of Example 6 is basically the same as that of Example 5, except that the borate coupling agent LD-100P is not added, that is, the premixing method of β-cyclodextrin and B2O3 in Example 6 is:
[0075] S31, AEO-3 and anhydrous ethanol were mixed in a mass ratio of 0.5:50, stirred evenly, and then B2O3 was added, and ultrasonic treatment was performed at 50°C, 300W, and 55kHz for 1 hour, and the mixture was allowed to stand at room temperature for 12 hours, and vacuum dried at 80°C to obtain modified B2O3; wherein the mass ratio of AEO-3 to B2O3 was 0.5:10;
[0076] S32. Modified B2O3 (Fe:B molar ratio of 1:0.0004) and 1.09 g of β-cyclodextrin were mixed, ground in a grinder for 2 h, heat treated at 200°C for 1 h under nitrogen, and naturally cooled to room temperature to obtain a β-cyclodextrin / B2O3 premix.
[0077] Example 7
[0078] The implementation method of Example 7 is basically the same as that of Example 5, except that AEO-3 is not added, that is, the premixing method of β-cyclodextrin and B2O3 in Example 7 is:
[0079] S31, mixing borate coupling agent LD-100P and anhydrous ethanol in a mass ratio of 1:50, stirring evenly, adding B2O3, ultrasonically treating at 50°C, 300W, 55kHz for 1h, standing at room temperature for 12h, and vacuum drying at 80°C to obtain modified B2O3; wherein the mass ratio of borate coupling agent LD-100P to B2O3 is 1:10;
[0080] S32. Modified B2O3 (Fe:B molar ratio of 1:0.0004) and 1.09 g of β-cyclodextrin were mixed, ground in a grinder for 2 h, heat treated at 200°C for 1 h under nitrogen, and naturally cooled to room temperature to obtain a β-cyclodextrin / B2O3 premix.
[0081] Comparative Example 1
[0082] The implementation of Comparative Example 1 is substantially the same as that of Example 1, except that the Tris-HCl buffer solution is replaced with pure water.
[0083] Comparative Example 2
[0084] The implementation of Comparative Example 2 is substantially the same as that of Example 1, except that no pre-sintering is performed.
[0085] Comparative Example 3
[0086] The implementation of Comparative Example 3 is substantially the same as that of Example 1, except that the raw materials for the hydrothermal reaction do not include a doping element, that is, the first doping element (MgO) is not added.
[0087] Comparative Example 4
[0088] The implementation of Comparative Example 4 is basically the same as that of Example 1, except that no secondary carbon supplementation is performed during the sand milling and spray drying process in step 3, that is, no second carbon source (β-cyclodextrin) is added.
[0089] Comparative Example 5
[0090] The implementation of Comparative Example 5 is basically the same as that of Example 1, except that the particle size D50 value in the sand milling in step 3 is controlled to be 700 nm.
[0091] Comparative Example 6
[0092] The implementation of Comparative Example 6 is basically the same as that of Example 1, except that the drying method in step 3 is changed to vacuum drying (drying temperature 100° C., drying time 10 h).
[0093] The sodium iron phosphate pyrophosphate positive electrode material obtained in the embodiment and the comparative example was subjected to a buckling test: the obtained sodium iron phosphate pyrophosphate positive electrode material, conductive carbon black (SuperP), and binder (PVDF) were dissolved in an appropriate amount of N-methylpyrrolidone solvent at a mass ratio of 8:1:1, the slurry was mixed and coated on aluminum foil, and after vacuum drying, it was cut into electrode sheets with a diameter of 14 mm and a surface density of 8 mg / cm 2At the same time, sodium sheet was used as negative electrode, glass fiber diaphragm was used as diaphragm, 1 mol / L NaClO4 (EC:DEC=1:1+5%FEC) solution was used as electrolyte, button cells (CR2032) were assembled in a glove box filled with argon, and then the assembled batteries were charged and discharged in the Blue Electric test system. The results are shown in Table 2. Figure 1 It is a charge-discharge specific capacity diagram (1.7-4.3V) of the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 at 0.1C; Figure 2 This is the charge and discharge specific capacity diagram of the sodium iron pyrophosphate positive electrode material prepared in Example 1 at 1C (1.7~4.3V).
[0094] Table 2
[0095]
[0096] From Table 2 and Figure 1 , 2 It can be seen that the compaction density and charge-discharge specific capacity of the sodium iron phosphate pyrophosphate positive electrode material prepared by the present invention are well improved, among which Examples 1, 2, 5 to 7 have the best effect, and the compaction density is 2.3 g / cm 3 The above, and the charge-discharge specific capacity at 0.1C and the discharge specific capacity at 1C are maintained at a good level, while the compaction density and charge-discharge capacity of the electrode material of the comparative example are poor, indicating that the preparation strategy of the invention can better improve the charge-discharge capacity and compaction density of the positive electrode material of the sodium ion battery; in addition, from the comparison of Examples 5 to 7 and Example 1, it can be seen that the sodium iron phosphate pyrophosphate positive electrode material obtained by the premixing treatment of β-cyclodextrin and B2O3 of the present invention has a higher compaction density and better electrochemical properties, among which the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 5 has the best performance.
[0097] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing sodium iron pyrophosphate positive electrode material, characterized in that: The following steps are involved: Step 1, hydrothermal reaction: adding raw materials into a Tris-HCl buffer solution, stirring evenly to obtain a mixed material, reacting, centrifuging, and obtaining a precursor; the raw materials include: a sodium source, an iron source, a phosphorus source, a first carbon source, and a first doping element; the amount of the raw materials added is 30-50wt% of the mass of the Tris-HCl buffer solution; Step 2, pre-sintering: pre-sintering the precursor under protective gas, first sintering at 60-150°C for the first stage, and then heating to 150-300°C for the second stage to obtain a pre-sintered intermediate with a carbon content of 0.1-0.8wt%; Step 3, sand milling and spray drying: premix β-cyclodextrin and B2O3 to obtain a β-cyclodextrin / B2O3 premix, add the β-cyclodextrin / B2O3 premix to the pre-sintered intermediate, sand mill and spray dry to obtain dry particles; wherein the premixing method of β-cyclodextrin and B2O3 is: S31, mixing a borate coupling agent, AEO-3 and anhydrous ethanol in a mass ratio of 1:0.3-0.8:40-80, stirring evenly, adding B2O3, ultrasonically treating at 40-70°C, 200-500W, 50-60kHz for 0.5-2h, standing at room temperature for 10-15h, and vacuum drying at 60-100°C to obtain modified B2O3; wherein the mass ratio of borate coupling agent, AEO-3 and B2O3 is 1:0.3-0.8:5-15; S32, mixing the modified B2O3 and β-cyclodextrin, grinding for 1 to 3 hours, heat treating at 150 to 300° C. for 0.5 to 2 hours under protective gas, and naturally cooling to room temperature to obtain a β-cyclodextrin / B2O3 premix; Step 4: high temperature sintering: sinter the dried particles at high temperature to obtain a sodium iron phosphate pyrophosphate positive electrode material with a carbon content of 1 to 2 wt%.
2. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In the step 1, the pH value of the Tris-HCl buffer solution is 8-9; the stirring time is 5-30 minutes; the reaction temperature is 120-200° C., and the reaction time is 6-18 hours.
3. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In the step 1, the molar ratio of Na, Fe and P in the sodium source, iron source and phosphorus source is 1:0.75:1; the molar ratio of the first doping element to Fe in the raw material is 0.001-0.002:
1.
4. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In the step 1, the sodium source is one or more of sodium carbonate, trisodium phosphate, sodium pyrophosphate, and sodium dihydrogen phosphate; the iron source is one or more of ferrous oxalate, ferrous phosphate, ferrous sulfate, and ferrous nitrate; the phosphorus source is one or more of ammonium dihydrogen phosphate, phosphoric acid, and ammonium phosphate; the first carbon source is one or more of glucose, sucrose, polyethylene glycol, and polyvinyl alcohol; and the first doping element is one or more of Mg, Ti, Cr, Zr, Al, V, Mn, Ni, and B.
5. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In the step 2, the protective gas is nitrogen, argon or argon-hydrogen mixed gas; The first sintering time is 1 to 3 hours, during which the gas flow rate is 1 to 20 L / min; the second sintering time is 1 to 8 hours, during which the gas flow rate is 1 to 10 L / min.
6. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In the step 3, the particle size D50 is controlled to be 80-500 nm by sand grinding; and the spray drying is performed by using a two-fluid spray gun or a centrifugal atomizer.
7. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In the step 4, the high temperature sintering temperature is 450-600° C. and the time is 5-12 hours.
8. A sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The material is prepared by the method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 1 to 7.
9. A battery, characterized in that: The positive electrode material of the battery is the sodium iron phosphate pyrophosphate positive electrode material as described in claim 8.
Citation Information
Patent Citations
Sodium ion battery positive electrode material sodium ferric pyrophosphate / carbon, synthesis method thereof and sodium ion battery
CN115196610A
MnO2 nanobelt / nitrogen-doped graphene aerogel composite material for supercapacitor as well as preparation method and application of MnO2 nanobelt / nitrogen-doped graphene aerogel composite material
CN113363086A
Preparation method of high-capacity and high-compaction lithium iron phosphate positive electrode material and prepared lithium iron phosphate positive electrode material
CN117800310A
Preparation method of spherical ferric sodium pyrophosphate positive electrode material
CN117819507A